2022
DOI: 10.7554/elife.79121
|View full text |Cite
|
Sign up to set email alerts
|

Anopheles homing suppression drive candidates exhibit unexpected performance differences in simulations with spatial structure

Abstract: Recent experiments have produced several Anopheles gambiae homing gene drives that disrupt female fertility genes, thereby eventually inducing population collapse. Such drives may be highly effective tools to combat malaria. One such homing drive, based on the zpg promoter driving CRISPR/Cas9, was able to eliminate a cage population of mosquitoes. A second version, purportedly improved upon the first by incorporating an X-shredder element (which biases inheritance towards male offspring), was similarly success… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 50 publications
1
34
0
Order By: Relevance
“…Homing drives and other fast drives that do not make any individuals nonviable were unaffected by the low-density growth rate. However, higher values will result in reduced suppression from any drive effects, which can have a negative effect on the outcome of a suppression drive release 65,68,70 . On the other hand, this effect could potentially increase the number of drive individuals, especially in suppression drives, and thus increase the speed of the wave.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Homing drives and other fast drives that do not make any individuals nonviable were unaffected by the low-density growth rate. However, higher values will result in reduced suppression from any drive effects, which can have a negative effect on the outcome of a suppression drive release 65,68,70 . On the other hand, this effect could potentially increase the number of drive individuals, especially in suppression drives, and thus increase the speed of the wave.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, we used discrete generations, which is not representative of most species, and considered a one-dimensional arena with no spatial heterogeneity. Complex lifecycle characteristics that are typical of many species 65,66 were excluded, and competition was also only considered between adults. It was also restricted to affecting female fecundity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drive outcomes in continuous space. Previous studies of suppression drive in continuous space have indicated that in many cases, suppression could be thwarted by the "chasing" phenomenon 42,[47][48][49][50]53 . When this occurs, wild-type individuals escape into areas where the population was previously suppressed by the drive.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that drive properties such as confinement can substantially vary in spatially explicit populations for frequency-dependent, confined drive systems [39][40][41] . Suppression gene drives have additional complexities in spatially explicit populations [42][43][44][45][46][47][48][49][50] . Perhaps the most prominent of these is the "chasing" effect, in which some wild-type individuals avoid suppression by the gene drive and reach areas of empty space where the population was previously suppressed by the drive.…”
Section: Introductionmentioning
confidence: 99%